Immunosuppressive Mechanisms of Regulatory B Cells - Catalán, Diego; Mansilla, Miguel Andrés; Ferrier, Ashley; Soto, Lilian; Oleinika, Kristine; Aguillón, Juan Carlos; Aravena, Octavio (Frontiers in Immunology, 2021)
Regulatory B cells (Bregs) is a term that encompasses all B cells that act to suppress immune responses. Bregs contribute to the maintenance of tolerance, limiting ongoing immune responses and reestablishing immune homeostasis. The important role of Bregs in restraining the pathology associated with exacerbated inflammatory responses in autoimmunity and graft rejection has been consistently demonstrated, while more recent studies have suggested a role for this population in other immune-related conditions, such as infections, allergy, cancer and chronic metabolic diseases. Initial studies identified IL-10 as the hallmark of Breg function, nevertheless the past decade has seen the discovery of other molecules utilized by human and murine B cells to regulate immune responses. This new arsenal includes other anti-inflammatory cytokines such IL-35 and TGF-, but also cell surface proteins like CD1d and PD-L1. In this review, we examine the main suppressive mechanisms employed by these novel Breg populations. We also discuss recent evidence that helps to unravel previously unknown aspects of the phenotype, development, activation and function of IL-10-producing Bregs, incorporating an overview on those questions that still remain obscure.